Differences in Growth on Math Curriculum-Based Measures Using Triannual Benchmarks. (June 2014) - Keller-Margulis, Milena A.; Mercer, Sterett H.; Shapiro, Edward S.
Recent research on annual growth measured using curriculum-based measurement (CBM) indicates that growth may not be linear across the year and instead varies across semesters. Numerous studies in reading have confirmed this phenomenon with only one study of math computation yielding a similar finding. This study further investigated the presence of differences in growth across triannual benchmarks using math computation and concepts and applications CBMs. Results indicated that there are differences in growth across semesters at certain grade levels with only first-grade computation and fourth-grade concepts and applications yielding linear growth. The practical implications for understanding student growth and for setting progress goals are addressed and future directions for research are suggested.